Potensi Daun Sambiloto (Andrographis paniculata Nees) Sebagai Anthelmitik Ascaridia Galli Pada Ayam Kampung (Gallus domesticus) - Nurul Hidayah; Miarsono Sigit; Maria Gabrielis Dua Bura (Jurnal Ilmiah Fillia Cendekia, 2021)
This study aimed to determine the anthelmintic potency of sambiloto leaf extract (Andrographis paniculata nees) against Ascaridia galli worms in vitro. The research sample was 125 Ascaridia galli worms obtained from the small intestine of native chickens. The research design used a completely randomized design with 5 treatments and 5 replications, namely the treatment group that was given physiological 0.9% NaCl (P1), the group that was given piperazine citrate (P2), the group that was given 20% concentration of sambiloto extract (P3). were given an extract concentration of 40% (P4) and the group given an extract concentration of 60% (P5). Observation of worm mortality was carried out every hour for 24 hours. The data obtained were analyzed using the One-way ANOVA test and followed by the 5% Duncan test. The results showed the sig. that is p 0.00 <0.05 means that there were significant differences between treatment groups. The 60% concentration of sambiloto leaf extract had high anthelmintic power and was comparable to the positive control (piperazine citrate). The conclusion of the study showed that the extract of sambiloto leaves (Andrographis paniculata nees) had anthelmintic power against Ascaridia galli worms in vitro. Keywords: Ascaridia galli worm, sambiloto leaf extract, anthelmintic